The OHI-s and dmft index and their relationship with salivary ph in students with special needs with intellectual disabilities at the Ann Sullivan center in Peru - Limo Dávila, Luis Angel (2017)
Objective: Salivary buffering capacity might be related to an individual’s susceptibility to Dental Caries. Aim: to find the association between the Oral Hygiene Index Simplified by Green & Vermillion (OHI-S) and the DMFT Index, and the salivary pH among students with special needs mentally retarted of the Center Ann Sullivan of Peru (CASP). Materials and Methods: A cros-sectional, prospective and clinical study was conducted in 45 students among 10 and 50 years old, who atended to the CASP, were assesed to determine the index of decayed, missing and filled teeth (DMFT Index) and plaque scores by OHI-S by Greene & Vermillion. 45 samples of saliva were collected, as a mínimum of 6ml. in order to measure its pH and buffer rate, by using a digital PHmeter. Results: for the whole group, it was registered a OHI-S = 2.0 which equals to a regular index; and a DMFT very low according to the World Health Organization. Ph rated were average 7.7. Though ANOVA parametric test, with a confidence level of 95%, it was determined a level of significance of 0.362 was determined for the relationship between the OHI-S and the salivary pH, and a level of 0.280 for the relationship between the DFMT Index and rhe salivary pH of the students attending to the CASP. Conclusions: Oral higiene status might be more related to their psychomotor disabilities.